A COMPARISON OF THE INTANGIBLE ASSET RELATED STANDARDS, IAS38, IVS210 AND ISA620 USING SIMILARITY ANALYSIS - GEORGIOU, Andreas (Studia Universitatis Babeș-Bolyai Oeconomica, 2024)
This article attempts to describe the standards dealing with intangible asset treatment by multiple regulatory bodies and subsequently compare them using content and similarity analysis. The specific standards debated are IAS 38 from an accounting perspective, IVS 210 from a valuation perspective, and ISA 620 from an auditing perspective. The similarity analysis is conducted using two tools. First, Voyant tools are used to perform a text similarity analysis of the standards' text bodies in portable document format. The technique employed is principal component analysis. The second tool is SPSS version 25, which employs various similarity and dissimilarity measures such as simple matching, Jaccard, and Euclidean coefficient, indicating that the similarity of the standards is rather mediocre in relative terms. JEL classification: O30, M40, M48